Strategic Design for Sumanene‐Derived Organic Cathodes with Tailored Redox Activity. Issue 4 (25th January 2022) - Jung, Ku Hyun; Kim, Ki Chul
Abstract: Despite the use of organic macromolecules in durable, high‐performance lithium‐ion battery cathodes, relevant studies are still lacking. Herein, sumanene, a representative macromolecule, and its derivatives are introduced through either individual or combined incorporation of two distinct functional groups, namely carbonyls and cyanides, to understand the effects of the functionalization strategy on their electrochemical redox properties. This computational investigation reveals that the combined incorporation of the two distinct redox‐active sites would synergistically improve the open‐circuit redox potential, ultimately leading to an exceptionally high theoretical performance of a sumanene‐derivative fully functionalized with carbonyl and cyanide. Furthermore, this study enables to draw meaningful conclusions on the three discharging stages, namely the fully charged, ongoing, and fully discharged stages. Clearly, the open‐circuit redox potential of a compound corresponding to the fully charged stage depends on its electron affinity that is dominantly contributed by the charging energy. During the discharging process, the redox potentials of the compounds gradually decrease with the increase in the number of bound Li atoms because of the Li‐induced weakening of its reductive ability owing to the continuous increase in its charging energy, leading to the cooperative contribution of charging and reorganization energies to the redox potential. At the end of the discharging process, the compound loses the cathodic activity with a negative redox potential, primarily owing to a sudden increase in solvation energy. Abstract : This study describes how the incorporation of distinct functional groups into a sumanene framework can synergistically improve the electrochemical properties of the organic compound. The density functional theory method combined with the strategic modeling approach effectively reveals the high redox activity of cyano‐carbonyl functionality uniformly distributed throughout the edge of the organic compound, suggesting a desired design direction for high‐performance lithium‐ion battery cathodes.